Chemistry solutions (ionic and molecular) (St. Louis : Coronet Films & Video)
Described solutions that are intimate part of our planet, from the vast solutions taht are oceans to the solutions that organisms depend on for their life functions
Copy available in DVD format
Executive producer, Ellica Rowen ; Script, Douglas L. Lieberman, Mel Waskin
Keywords: Solution (Chemistry).; Ionic solutions; Molecular theory